Cultural Adaptation In Literary Translation: An Analysis Of The Novels - Siregar, Ayunda Putri Amirah; Surayya, Azizah (Philosophiamundi, 2023)
Translation is a timeless practice that facilitates communication between diverse linguistic and cultural communities. With the increasing global interaction, it becomes imperative for translators to not only decipher words but also comprehend the underlying cultural beliefs, values, and norms. This paper delves into the intricacies of literary translation, emphasizing the importance of preserving the emotional and psychological impact of the original text for the target language reader. To achieve this, translators often employ adaptation techniques to harmonize cultural elements from the source language into the target language, ensuring familiarity and resonance with the intended audience. This research focuses on the novel "Api Tauhid" by Habiburrahman El Shirazy, exploring shifts in translation, specifically regarding cultural content. This Study using Qualitative Method. Data was collected from the Indonesian source text and its Local Translation, revealing various cultural categories that were adapted to suit the target language. The purpose of this research is to find out and also adapt cultural elements that may have different backgrounds from other cultures. These categories encompass ecological, material culture, social culture, and social organization aspects, shedding light on the intricacies of preserving cultural nuances in translation. The results of the analysis above, it can be concludedthat there are 38 data on the number of cultural categories in the vocabulary in the novel Api Tauhid. The cultural categories proposed for the data in the novel are ecology, material culture, social culture, social organization, customs and other cultures. The material culture category is another cultural category that is most often found in the novel.